Why Face-to-Face Still Matters : The Persistent Power of Cities in the Post-Pandemic Era - Reades, Jonathan; Crookston, Martin (Book collections on Project MUSE., 2021)
What do cities do that suburbs or exurbs can't? Tracking more than a century's worth of thinking across infrastructures, markets, and changing technologies, this book drills down into the realities of modern city business life to explore why central places have come to dominate economic life in the 21st Century. COVID-19 has meant it's a difficult time to be putting the case for the importance of Face-to-Face, but the book outlines how it can help us--often in unobserved ways--to negotiate uncertainty and to 'seal the deal'. Using interviews with staff and business leaders from high-profile industries to bring it to life, the book argues for the value of the 'right' location during and after the pandemic, and explains why ICT has transformed both businesses, and our cities and towns, and yet also changed little about the underlying challenges of business life. This accessible book gives readers including developers, investors, and policy-makers essential tools for thinking about the future of places ranging from market towns to great World Cities.